Enhanced mechanical properties of chitosan/EDTA-gO nanocomposites thin films - Syuhada, N.I.; N.M., Huang; S., Vijay Kumar; H.N., Lim; Rahman, S.A.; G.S., Thien; Ibrahim, N.A.; Ahmad, M.; P., Moradihamedani (Universiti Kebangsaan Malaysia, 2014)
Nanocomposite thin films of chitosan/graphene oxide (CS/GO) and chitosan/ EDTA-GO (CS/EDTA-GO) were prepared by environmental friendly method and the properties were compared. The experimental results showed fine dispersion of GO and EDTA-GO in CS matrix and some interaction occur between the filler and the CS matrix that leads to better distribution of stress transfer. At 0.5 wt. %, both CS/GO and CS/EDTA-GO experienced maximum tensile stress by 51 and 71% compared with CS. Moreover, the elongation at break for both nanocomposites increases and the amount of filler increases.